ANALISIS PENGEMBANGAN KECERDASAN EMOSIONAL UNTUK MENINGKATKAN SIKAP SOSIAL SISWA KELAS VI DI MIN 1 KOTA PALEMBANG - Rizki Febriani , Aulia; Putri, Nabila; Mubaroakh, Pintaria; Damayanti, Alpina; Tasya Jadidah, Ines (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2024)
This study aims to determine the development of emotional intelligence to improve students' social attitudes, this research uses a type of qualitative research, data collection techniques using observation, interviews, documentation and data triangulation. the sample used in this study VI (A) class students totaling 25 students, and also the class teacher. The results of this research show that: A). The influence of emotional intelligence on student attitudes can form good social relationships, a high level of emotional intelligence can create a positive attitude in students, emotional intelligence on social attitudes is different between younger and older students. B). Emotional Intelligence Can Shape Social Attitudes, the contribution of emotional intelligence in shaping students' social attitudes including, Understanding Emotions, Having a Sense of empathy, and creating quality social relationships, The correlation between the level of emotional intelligence of students can affect students' positive attitudes towards cooperation and care between students. Teachers have a role in supporting the development of students' emotional intelligence by giving special attention.